Towards a Diagnostic Toolkit for the Language of Agency. (2nd April 2016) - Konopasky, Abigail W.; Sheridan, Kimberly M.
ABSTRACT: Agency—broadly, the capacity to produce effects—is a critical aspect of human activity, yet its multifaceted character makes analysis difficult. Drawing from functional linguistics, we propose a linguistic toolkit for analyzing the degree to which and manner in which speakers represent themselves as acting intentionally and autonomously. After a brief review of relevant agency literature, we propose three sets of grammatical tools, demonstrating their efficacy with a brief case study of 4 adult secondary learners' educational narratives. We find that our toolkit offers insight both across contexts within an individual and across individuals in a single context.